1988
DOI: 10.1073/pnas.85.16.6107
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin 4 induces membrane Thy-1 expression on normal murine B cells.

Abstract: Thy-1, a cell-surface glycoprotein of undetermined function, is expressed in relatively large amounts on mouse thymocytes, peripheral T cells, and neurons. It is widely used as a marker to distinguish peripheral T cells from B cells in mice. We show here that, in five distinct mouse strains

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

1992
1992
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…The biological function of Thy1 is poorly understood, but it may likely be involved in signal transduction from the plasma membrane, because it was shown that thymocytes of Thy1-deficient mice exhibit augmented TCR signaling and impaired T cell differenti-ation (30). Other studies showed that LPS+IL-4-stimulated B cells, but not LPS-stimulated B cells, upregulate Thy1 (31,32). We confirm and extend these findings by showing that STAT6 expression in B cells is required for this effect.…”
Section: Discussionmentioning
confidence: 99%
“…The biological function of Thy1 is poorly understood, but it may likely be involved in signal transduction from the plasma membrane, because it was shown that thymocytes of Thy1-deficient mice exhibit augmented TCR signaling and impaired T cell differenti-ation (30). Other studies showed that LPS+IL-4-stimulated B cells, but not LPS-stimulated B cells, upregulate Thy1 (31,32). We confirm and extend these findings by showing that STAT6 expression in B cells is required for this effect.…”
Section: Discussionmentioning
confidence: 99%
“…It increases the expression of class II MHC molecules in B cells (18), enhances expression of CD23 (19), upregulates the expression of the IL-4 receptor (20), and, in association with lipopolysaccharide, allows B cells to express Thy 1 (21). It also acts as a co-mitogen for B cell growth (22).…”
Section: Introductionmentioning
confidence: 98%
“…For example, IL-4 plays a central role in promoting the differentiation of Ag-stimulated naive T cells to develop into Th2 cells and is also responsible for the induction of B cell Ig class switching to IgE (1). In addition, IL-4 acts as a comitogen for T and B cell growth (2,3). Like other cytokines, IL-4 induces the activation of signal transduction pathways that are used to regulate cell growth and differentiation (4).…”
Section: Fes Mediates the Il-4 Activation Of Insulin Receptor Substramentioning
confidence: 99%
“…Because the basal activities of p70 S6K and Akt/PKB can be deprived in murine myeloid 32D/IRS-1 (2) cells under serum/IL-3 starvation, we generated 32D/IRS-1 stable transfectants expressing vector (control 3, 4), wild-type (Fes WT 3, 5), or kinase-inactive Fes (Fes KE 2,12,24) to study the activation of p70 S6K and Akt/PKB in response to IL-4. As has been previously shown (40,41), IL-4 can induce phosphorylation of Akt on Ser 473 (Fig.…”
Section: Kinase-inactive Fes Inhibits the Activation Of P70 S6k But Nmentioning
confidence: 99%